Agama dan Budaya - Sumarto Sumarto (Pascasarjana IAIN Metro, 2017)
Religion and culture in different perspectives and similar perspectives have interpretations that can lead to conflicts / problems. Many religious and cultural cases that occur because of wrong interpretation or just simply follow-up. In this paper will present the understanding of religion and culture in parsialistik and integralistik view that must be instilled in school / madrasah culture. Schools should instill early values of the students, so that they will be able to live up to these key values in real life in society- whatever their profession. School activities, programs, and environments should teach students about key values, so they not only know good bad, but run them in reality and everyday interactions in school. When students are accustomed to the principal behaviors, attitudes, and speeches in school, the main values can be a culture for them, which will not be easily faded by the exposure of negative cultures. Conversely, the main culture will be a valuable capital for the life of students later. Because, noble culture will lead to success and even to happiness.